Optimizing the biosynthesis of oxygenated and acetylated Taxol precursors in Saccharomyces cerevisiae using advanced bioprocessing strategies. Issue 1 (7th October 2020) - Walls, Laura E.; Malcı, Koray; Nowrouzi, Behnaz; Li, Rachel A.; d'Espaux, Leo; Wong, Jeff; Dennis, Jonathan A.; Semião, Andrea J. C.; Wallace, Stephen; Martinez, José L.; Keasling, Jay D.; Rios‐Solis, Leonardo
Abstract: Taxadien‐5α‐hydroxylase and taxadien‐5α‐ol O ‐acetyltransferase catalyze the oxidation of taxadiene to taxadien‐5α‐ol and subsequent acetylation to taxadien‐5α‐yl‐acetate in the biosynthesis of the blockbuster anticancer drug, paclitaxel (Taxol®). Despite decades of research, the promiscuous and multispecific CYP725A4 enzyme remains a major bottleneck in microbial biosynthetic pathway development. In this study, an interdisciplinary approach was applied for the construction and optimization of the early pathway in Saccharomyces cerevisiae, across a range of bioreactor scales. High‐throughput microscale optimization enhanced total oxygenated taxane titer to 39.0 ± 5.7 mg/L and total taxane product titers were comparable at micro and minibioreactor scale at 95.4 ± 18.0 and 98.9 mg/L, respectively. The introduction of pH control successfully mitigated a reduction of oxygenated taxane production, enhancing the potential taxadien‐5α‐ol isomer titer to 19.2 mg/L, comparable with the 23.8 ± 3.7 mg/L achieved at microscale. A combination of bioprocess optimization and increased gas chromatography‐mass spectrometry resolution at 1 L bioreactor scale facilitated taxadien‐5α‐yl‐acetate detection with a final titer of 3.7 mg/L. Total oxygenated taxane titers were improved 2.7‐fold at this scale to 78 mg/L, the highest reported titer in yeast. Critical parameters affecting the productivity of the engineered strain were identified across a range of scales, providing a foundation for the development of robust integrated bioprocess control systems. Abstract : An interdisciplinary approach was applied for the construction and optimization of the early stages of a Taxol® biosynthetic pathway in Saccharomyces cerevisiae, across a range of bioreactor scales. Through design of experiments guided high‐throughput microscale screening, titers of early precursors were enhanced. Critical parameters affecting productivity were identified across a range of scales. Strategic optimization and control of such parameters at 1 L bioreactor scale facilitated detection of the third Taxol intermediate, taxadien‐5α‐yl‐acetate, under industrially relevant conditions.